In a world of changes: using a new visual research method for exploring employees’ attitudes towards the organizations they work in - Haller-Hayon, Orit (Kultura-Społeczeństwo-Edukacja, 2018)
In the age of globalization, employees are required to adapt themselves to changes inthe working world. Employees change their working placesquite often; therefore, they have less stability in the organizations they work in. This situation might influence their general attitudes toward the organizations and particularly their personal perceptions about their organizational positions. In turn,this affects their motivation, loyalty, health etc. The aim:To present three studies which were carried out in three distinct periods of time regarding Israeli employees’ perceptions of their organizational positions, incorporating a new visual method developed by the author.The population included technology managers, registered hospital nurses and educators. The common research methods (questionnaires and interviews) facilitate the examination of visible attitudes but are less effective for those which are hidden. The visual method was based on the drawing of a fruit tree, and suggested an indirect way of exploring the participants’ attitudes. Results and conclusion: The participants’ interpretations raised a diversity of themes about their organizational positions, depending on the type of organization and their stability in the workplace. This enabledthe gaining of a deep level of knowledgeaboutthe employees’ attitudes in an indirect way.